Intermediates and shunt products of massiliachelin biosynthesis in Massilia sp. NR 4-1 - Till Steinmetz; Blaise Kimbadi Lombe; Markus Nett (Beilstein Journal of Organic Chemistry, 2023)
Siderophores are small molecules secreted by microorganisms in order to scavenge iron from the environment. An example is the thiazoline-containing natural product massiliachelin, which is produced by Massilia sp. NR 4-1 under iron-deficient conditions. Based on experimental evidence and genome analysis, it was suspected that this bacterium synthesizes further iron-chelating molecules. After a thorough inspection of its metabolic profile, six previously overlooked compounds were isolated that were active in the chrome azurol S (CAS) assay. Mass spectrometric measurements and nuclear magnetic resonance spectroscopic analyses identified these compounds as possible biosynthetic intermediates or shunt products of massiliachelin. Their bioactivity was tested against one Gram-positive and three Gram-negative bacteria.